Pengelolaan Lubuk Larangan sebagai Upaya Konservasi Perairan di Desa Rantau Pandan Kabupaten Bungo, Jambi - Diana Sari; Indra Junaidi Zakaria; Wilson Novarino (Universitas Riau, 2016)
Abstrak: This study aims to analyze governance and harvest fish Lubuk Larangan Rantau Pandan Village Bungo Resindence. This research is carried in March-August 2015 in a river of Rantau Pandan Village Bungo Residence, Jambi. The metod that is used is survey method. Then using SWOT analysis with regard to Lubuk Larangan with assesses each internal and external factors. Based on the observation efforts made by communities around the bottom of the prohibition only covers the preservation of fish species alone and the lack of cooperation between the government and the surrounding community.